2007
DOI: 10.1038/labinvest.3700674
|View full text |Cite
|
Sign up to set email alerts
|

ROCK-II mediates colon cancer invasion via regulation of MMP-2 and MMP-13 at the site of invadopodia as revealed by multiphoton imaging

Abstract: The ROCK-II isoform of Rho's downstream effector, Rho kinase, has been linked with greater invasion and metastasis in solid tumors. We have previously shown that ROCK-II is overexpressed at the advancing edge of colon cancers. The mechanism whereby ROCK-II contributes invasion, particularly in the setting of colon cancer, remains to be elucidated fully. To better understand its contribution, we evaluated ROCK-II expression in both non-malignant (NCM460 and IEC-6) and malignant (Caco-2 E, SW620, and HCT-116) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 39 publications
3
50
2
2
Order By: Relevance
“…However, zymogram studies did not show a correlation between matrix metalloproteinase (MMP) expression and pY14Cav1 expression or Rho activation state in these tumor cells (data not shown). Indeed, MDA-231 cells have recently been shown to follow a proteolytic, mesenchymal migratory mode (28) and HCT116 cells to exhibit ROCKII-dependent regulation of invasion, MMP-2 and MMP-13 activity, and invadopodia formation (29). Aside from increased binding of prostate PC3 cells to collagen types I and IV relative to DU145 cells, we detected no significant changes in adhesion to extracellular matrix components between the tumor cell lines studied (Supplementary Fig.…”
Section: Cav1 Andmentioning
confidence: 65%
See 1 more Smart Citation
“…However, zymogram studies did not show a correlation between matrix metalloproteinase (MMP) expression and pY14Cav1 expression or Rho activation state in these tumor cells (data not shown). Indeed, MDA-231 cells have recently been shown to follow a proteolytic, mesenchymal migratory mode (28) and HCT116 cells to exhibit ROCKII-dependent regulation of invasion, MMP-2 and MMP-13 activity, and invadopodia formation (29). Aside from increased binding of prostate PC3 cells to collagen types I and IV relative to DU145 cells, we detected no significant changes in adhesion to extracellular matrix components between the tumor cell lines studied (Supplementary Fig.…”
Section: Cav1 Andmentioning
confidence: 65%
“…Regulation of tumor cell invasion by Rho/ROCK signaling may therefore involve Cav1-dependent FA turnover in protrusive tumor cell domains of cells invading via a mesenchymal migratory mode in addition to matrix deformation and proteolysisindependent cell invasion (10,11). In addition, Rho/ROCK signaling regulates mRNA translocation to tumor cell protrusions, the invasive response to hypoxic conditions and invadopodia formation (5,8,29), suggesting that it may play multiple important roles in tumor cell migration and invasion. The critical role described here for pY14Cav1, as a regulator of Rho activation and of Src-dependent and ROCK-dependent tumor cell migration and invasion, provides a mechanistic explanation for the close association between Cav1 expression and poor survival and distant metastasis in various human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations could not be fully explained by differences in proliferation or apoptosis. In keeping with this, it was recently reported that invadopodia are not important for cell viability (Weaver, 2006;Vishnubhotla et al, 2007). However, we only analyzed tumors that were isolated at the end point of the assay, which may have masked differences in cell death and proliferation that occurred at an earlier stage.…”
Section: Discussionmentioning
confidence: 84%
“…Podosomes/invadopodia are found in various mammalian cells such as macrophages, osteoclasts and vascular smooth muscle cells (Linder and Aepfelbacher, 2003). They are also detected in various human cancer cells, including breast, colon, and head and neck cancer cell lines (Artym et al, 2006;Bharti et al, 2007;Clark et al, 2007;Vishnubhotla et al, 2007) and in Src-transformed fibroblasts (Abram et al, 2003). The activation of Src is essential for the formation of these structures (Weaver, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…SPP1, up-regulated in metastasis (see inset in Figure 4), is a well-studied protein that triggers intracellular signaling cascades upon binding with various integrin heterodimers, promotes cell migration when it binds CD44, and when binding the alpha-5/beta-3 dimer in particular, promotes angiogenesis, which is associated with the metastatic phenotype of many cancers [35]. MMP proteins are involved in the breakdown of ECM, particularly collagen which is the primary substrate at the invasive edge of colorectal tumors [36]. MMP-1 has an inhibitory effect on Vitronectin (red line), hence the loss of expression of MMP-1 may "release the brake" on Vitronectin, which in turn may increase the activity of the alpha-v/beta-5 integrin heterodimer.…”
Section: Subnetwork and State Functions Indicative Of Metastasis In mentioning
confidence: 99%